Prediction of overshoot and crosstalk of low-voltage GaN HEMT using analytical model - Wu, Yingzhe (2022)
Ultra-fast switching speed and low switching loss of the gallium nitride high electron mobility transistors enable the realisation of high power density converter with excellent conversion efficiency. However, the rapid switching transition leads to significant overshoot and crosstalk issues that can degrade the performance of the devices. To facilitate the evaluation of these effects on low-voltage gallium nitride devices, this paper develops an analytical model to predict overshoot and crosstalk during switching transitions accurately and efficiently. The model is constructed based on the detailed circuit deduction of various stages of the device's switching process. It also considers the voltage-dependent junction capacitances as well as the forward and the reverse transconductances. The simulated results obtained from the model are validated experimentally. With the model, the impacts of parasitic elements, especially the power loop inductance, on voltage/current overshoots and spurious voltage due to crosstalk can be easily evaluated, which provides valuable design guidelines for power conversion applications using low-voltage gallium nitride high electron mobility transistor.